The Tucson ungrouped iron meteorite and its relationship to chondrites - Kurat, G. (2010)
Tucson is an enigmatic ataxitic iron meteorite, an assemblage of reduced silicates embedded in Fe-Ni metal with dissolved Si and Cr. Both, silicates and metal, contain a record of formation at high temperature (∼1800 K) and fast cooling. The latter resulted in the preservation of abundant glasses, Al-rich pyroxenes, brezinaite, and fine-grained metal. Our chemical and petrographic studies of all phases (minerals and glasses) indicate that they have a nebular rather than an igneous origin and give support to a chondritic connection as suggested by Prinz et al. (1987). All silicate phases in Tucson apparently grew from a liquid that had refractory trace elements at approximately 6–20 × CI abundances with nonfractionated (solar) pattern, except for Sc, which was depleted (∼1 × CI). Metal seems to have precipitated before and throughout silicate aggregate formation, allowing preservation of all evolutionary steps of the silicates by separating them from the environment. In contrast to most chondrites, Tucson documents coprecipitation of metal and silicates from the solar nebula gas and precipitation of metal before silicates—in accordance with theoretical condensation calculations for high-pressure solar nebula gas. We suggest that Tucson is the most metal-rich and volatile-element-poor member of the CR chondrite clan.